Perspectiva do letramento : mudanças e permanências nos livros didáticos de alfabetização - Cornélio, Shenia D'Arc Venturim (2015)
This doctoral thesis integrates a set of academic productions developed in the field of language, focused on an enunciative-discursive approach, in Education and Languages research line, of the Post Graduate Program in Education of the Federal University of Espirito Santo. Is a documentary study, guided by the dialogic perspective that aims to understand changes and / or stays in the proposals for teaching literacy books with the adoption of literacy perspective as the guiding literacy policies at the federal government. It is based on Bakhtin's language approach, particularly based on the notion of statement discussed by this author, arguing that the statements are the real links in the communication chain that are determined by the different fields of human activities. It performs the study of PNLDs 2007 and 2010, analysis of the notices, the textbook guides about the more and the less distributed books by the Ministry of Education and the teachers' manuals of these programs. The analyzes allowed the identification of changes in use as the less distributed textbook using the syllabic method and the more distributed book using the analytical method. Both books start from texts to perform a school work with the sound relations and letters and sounds and letters for teaching knowledge of the writing system, with differences in the way they organize teaching in a systematic and unsystematic way. Another noticeable aspect is the search for reconciliation of different theoretical principles of literacy proposals